2020
DOI: 10.1080/20002297.2020.1775333
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity in fim and mfa gene clusters between Porphyromonas gingivalis and Porphyromonas gulae, as a potential cause of host specificity

Abstract: Background: Periodontopathic bacteria Porphyromonas gingivalis in humans and Porphyromonas gulae in animals are phylogenetically close and commonly have FimA and Mfa1 fimbriae. However, little is known about how fimA and mfa1 are phylogenetically different between P. gingivalis and P. gulae. Here, we examined phylogenetic diversity in their fim and mfa gene clusters. Methods: Twenty P. gulae strains were isolated from the periodontal pocket of 20 dogs. For their genomic information, along with 64 P. gingivalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…The fimA gene has been classified into six genotypes (I to V, and Ib) based on either PCR using genotype-specific primers, or on the presence or absence of restriction enzyme cleavage [8]. However, genotype Ib is now unified into genotype I because of their similar antigenicity and overall DNA sequences [13,14]. Studies from many countries have reported that genotypes II and IV are predominantly detected in patients with severe periodontitis, whereas genotype I is prevalent in healthy or mild periodontitis subjects [8,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The fimA gene has been classified into six genotypes (I to V, and Ib) based on either PCR using genotype-specific primers, or on the presence or absence of restriction enzyme cleavage [8]. However, genotype Ib is now unified into genotype I because of their similar antigenicity and overall DNA sequences [13,14]. Studies from many countries have reported that genotypes II and IV are predominantly detected in patients with severe periodontitis, whereas genotype I is prevalent in healthy or mild periodontitis subjects [8,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The NJ‐cladograms and NJ‐phylograms of 50 fimA genotypes and 133 FimA serotypes all showed the same eight distinct clusters A–H along with some outliners (possibly hybrid strains) corresponding to type A of P. gulae and seven human fimA /FimA P. gingivalis subtypes, including two II‐subtypes (a and b) for nomination. Cluster A, containing all six P. gulae animal isolates with fimA type A (Fujiwara‐Takahashi et al., 2020). We hereby propose that it possibly represents the ancestral sequence of the fimA gene as frequently found and especially in monkeys.…”
Section: Resultsmentioning
confidence: 99%
“…In dogs, periodontal disease is mainly associated with the presence of P. gulae , which was originally thought to be the animal biotype of P. gingivalis ; however, it was also found to colonize human oral cavity [ 69 ]. P. gulae has similar characteristics as P. gingivalis [ 70 ], which may result in the potential transmission between animals and their owners [ 23 ]. It possesses a broad spectrum of pathogenic properties such as lipopolysaccharide, haemagglutinins, fimbriae and proteases [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, Nomura et al [ 73 ] found that certain FimA types of fimbrial protein of canine P. gulae were phylogenetically close to those of P. gingivalis . Moreover, Fujiwara-Takahashi et al [ 70 ] found that FimA types I, III, and IV in P. gingivalis were close to types A, B, and C, respectively, in P. gulae in dogs. Iwashita et al [ 74 ] identified the fimA genotypes in feline P. gulae isolates, as well.…”
Section: Discussionmentioning
confidence: 99%